2012
DOI: 10.1016/j.sjbs.2012.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salt on survival and P-solubilization potential of phosphate solubilizing microorganisms from salt affected soils

Abstract: A total of 23 phosphate solubilizing bacteria (PSB) and 35 phosphate solubilizing fungi (PSF) were isolated from 19 samples of salt affected soils. The ability of 12 selected PSB and PSF to grow and solubilize tricalcium phosphate in the presence of different concentrations of NaCl was examined. Among 12 PSB, Aerococcus sp. strain PSBCRG1-1 recorded the highest (12.15) log viable cell count at 0.4 M NaCl concentration after 7 days after incubation (DAI) and the lowest log cell count (1.39) was recorded by Pseu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 17 publications
1
35
0
Order By: Relevance
“…The use of phosphate solubilizing microorganisms as biofertilizers represents a promising strategy to improve world food and at the same time conserve the environment. The beneficial microorganisms solubilize phosphorus in vitro, increasing the bioavailability of insoluble phosphorus from soil to be used by plants [55][56][57][58]. It has been reported an efficient treatment with Aspergillus niger, which stimulated significantly the growth of cabbage cultures, increasing roots and shoots length, weights of fresh and dry shoots [59].…”
Section: Discussionmentioning
confidence: 99%
“…The use of phosphate solubilizing microorganisms as biofertilizers represents a promising strategy to improve world food and at the same time conserve the environment. The beneficial microorganisms solubilize phosphorus in vitro, increasing the bioavailability of insoluble phosphorus from soil to be used by plants [55][56][57][58]. It has been reported an efficient treatment with Aspergillus niger, which stimulated significantly the growth of cabbage cultures, increasing roots and shoots length, weights of fresh and dry shoots [59].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Xiao et al (2013) demonstrated the capability of Aspergillus niger WHAK1 to solubilize rock phosphate over a wide range of temperature, pH, salinity, and desiccation. Srinivasan et al (2012) demonstrated the capability of Aspergillus terreus to solubilize rock phosphate under salt stress, and Kanse et al (2015) found a similar performance in Talaromyces funiculosus under different concentrations of NaCl, as well as a relatively high tolerance to the presence of fungicides. Therefore, stress-tolerant fungi are of particular interest to improve the availability of P in crops under changing environmental conditions (Babu and Reddy 2011;Xiao et al 2013).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 83%
“…Different soil stressors such as increase in sodium chloride and pH influences phosphorus solubilization [40]. Despite the negative effect of ZnO nanoparticles on phosphate-solubilizing bacteria which directly correlated with reduced phosphate content in the amended ultisol, Pseudomonas aeruginosa and P. alcaligenes were isolated from the ultisol and loam soils.…”
Section: Influence On Available Phosphate and Phosphate-solubilizing mentioning
confidence: 98%